The Influence of Classroom Management Implementation in the Implementation of Student Learning in the Department of Islamic Education Management, Faculty of Tarbiyah and Teacher Training UIN Syarif Hidayatullah Jakarta - Hidayat; Hana Habibah Ma'mun; Irawan (Zona Education Indonesia, 2023)
Teachers and instructors who have the necessary skills and expertise are more likely to create a conducive learning environment and manage their classes effectively, resulting in optimal student learning behavior. This article presents the findings of a study conducted at the Department of Islamic Education Management, Faculty of Tarbiyah and Teacher Training, UIN Syarif Hidayatullah Jakarta, with the aim of examining the impact of classroom management practices on student learning behavior. This study used a quantitative approach, with an Ex Post Facto research design and a correlational descriptive research model. This research involved all students enrolled in the Department of Islamic Education Management, Faculty of Tarbiyah and Teacher Training, with a sample of 31 students. Data collection was carried out through questionnaires on classroom management practices and learning behavior scales. The collected data is analyzed using quantitative methods, especially the application of simple linear regression formulas. The research findings show a clear correlation between the implementation of effective classroom management and the learning behavior of students where . In essence, the more proficient class management is implemented, the more positive the impact on student behavior during the learning process.